Characterization of a novel HLA‐B allele (HLA‐B*18:108) by intron–exon sequencing of the HLA‐B locus. Issue 3 (22nd July 2015) - Curcio, M.; Sciarrino, R.; Biagini, C.; Marchetti, L.; Gobbo, F.; Scatena, A.; Presciuttini, S.
<x xml:space="preserve">Abstract</x> HLA‐B*18:108 has two nucleotide changes from B*18:01:01:02 at nt 430 where A → G and nt 431 where G → A.